PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TURNAMEN GAME TIM (TGT) UNTUK MENINGKATKAN KEMAMPUAN BERBICARA SISWA KELAS XI IPA 2 SMAN 9 PEKANBARU - Yuhartati Yuhartati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2017)
Based on experience for teaching english in SMAN 9 Pekanbaru, the authors apply the method of discussion. The author hopes that through this method, students will actively speak english, along with a idea or their ideas about the topic being discussed. But in fact, the authors found symptoms in the learning process subjects in English as follows: Low ability skills of English speaking students of class XI IPA 2 SMAN 9 Pekanbaru, as seen from the average value of students who have not reached the KKM of the school is 65. Some students are still reluctant and even to shut up when they were spoken to by the teacher or anyone else in english. In fact, judging from the mastery of vocabulary, the student should be able to speak english even though a series of very simple sentences. A total of 15 students or 45.0% of 38 students had difficulty in speaking english so they have not been able to achieve a predetermined KKM. Their most difficult students who speak the english language with its own language to tell about experiences or events that happened. This research is a class act (class action reseach). Subjects in this study were students of class XI IPA2 as many as 33 students. In order to study this class action work well without barriers obstructing the smooth running of the study, researchers compiled stages are passed in classroom action research, namely: (1) planning/ preparatory actions; (2) Implementation of the action; (3) observation, and reflection. Based on the results of the discussion and analysis as presented in chapter IV can be concluded that the implementation of cooperative learning model of team game tournament (TGT) may increase the ability of speak english on english tuition class XI students IPA 2 SMAN 9 Pekanbaru. Based on the survey results revealed that the ability speaking english students before action classical gained an average of 58.5, an increase in the first cycle to 67.3, while the increase also occurred in the second cycle with an average of 87.6 classical.